Accounting information systems - Hall, James A.
Providing coverage of accounting information systems and related technologies, this text features an early presentation of transaction cycles plus a special emphasis on ethics, fraud, and the modern manufacturing environment. The Enterprise Resource Planning system, SAP, has been integrated into this edition. Featuring screen shots of the SAP Website in the text and a password that links students to a specially created SAP Website, the text provides hands-on exposure to ERP. Also included are chapters on such topics as the Resources, Events, and Agents (REA) approach, Enterprise Resource Planning (ERP) systems, and Electronic Commerce systems. Hall assumes that the student is familiar with fundamental accounting principles and basic computer concepts and terminology and has been exposed to computer programming. The focus is on the needs and responsibilities of accountants as end users of systems, systems designers, and auditors.